The roles of extracellular vesicles in gastric cancer development, microenvironment, anti-cancer drug resistance, and therapy - Tingting Huang; Chunli Song; Lei Zheng; Ligang Xia; Yang Li; Yiwen Zhou (Molecular Cancer, 2019)
Abstract Gastric cancer (GC) is one of the leading causes of cancer-related death in both men and women due to delayed diagnosis and high metastatic frequency. Extracellular vesicles (EVs) are membrane-bound nanovesicles which are released by cells into body fluids such as plasma, saliva, breast milk, cerebrospinal fluid, semen, urine, lymphatic fluid, amniotic fluid, sputum and synovial fluid. EVs deliver almost all types of biomolecules such as proteins, nucleic acids, metabolites, and even pharmacological compounds. These bioactive molecules can be delivered to recipient cells to influence their biological properties, modify surrounding microenvironment and distant targets. The extensive exploration of EVs enhances our comprehension of GC biology referring to tumor growth, metastasis, immune response and evasion, chemoresistance and treatment. In this review, we will sum up the effects of GC-derived EVs to the tumor microenvironment. Moreover, we will also summarize the function of microenvironment-derived EVs in GC and discuss how the bidirectional communication between tumor and microenvironment affect GC growth, metastatic behavior, immune response, and drug resistance. At last, we prospect the clinical application viewpoint of EVs in GC.